2014
DOI: 10.1051/0004-6361/201423929
|View full text |Cite
|
Sign up to set email alerts
|

POISSON project

Abstract: Context. As part of the Protostellar Optical-Infrared Spectral Survey On NTT (POISSON) project, we present the results of the analysis of low-resolution near-IR spectroscopic data (0.9-2.4 μm) of two samples of young stellar objects in the Lupus (52 objects) and Serpens (17 objects) star-forming clouds, with masses in the range of 0.1 to 2.0 M and ages spanning from 10 5 to a few 10 7 yr.Aims. After determining the accretion parameters of the targets by analysing their H i near-IR emission features, we added t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 60 publications
5
46
2
Order By: Relevance
“…Tables A.1-A.2). Accretion rate estimates are only available for some targets (e.g., Antoniucci et al 2011Antoniucci et al , 2014Frasca et al 2015). Here we compare these results with our estimates.…”
Section: Comparison With Other Methodsmentioning
confidence: 79%
See 3 more Smart Citations
“…Tables A.1-A.2). Accretion rate estimates are only available for some targets (e.g., Antoniucci et al 2011Antoniucci et al , 2014Frasca et al 2015). Here we compare these results with our estimates.…”
Section: Comparison With Other Methodsmentioning
confidence: 79%
“…3 shows the comparison between the values oḟ M acc for Chamaeleon I targets derived here and those from the POISSON survey (Antoniucci et al 2011(Antoniucci et al , 2014 and the Gaia-ESO survey (GES, Frasca et al 2015). The POISSON survey used infrared spectra and the luminosity of the Brγ and Paβ emission lines to derive L acc , and obtainedṀ acc assuming the stellar parameters for the targets from Luhman (2007).…”
Section: Comparison With Other Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the real origin of these lineswhether in accretion columns and spots, or in ionized winds -is still uncertain, it has been shown that their intrinsic luminosity scales with L acc in T Tauri stars (Herczeg & Hillenbrand 2008;Alcalá et al 2014). As such they have been widely used to indirectly derive L acc and consequently the mass accretion rate (Ṁ acc ) in sources with known stellar parameters (e.g., Antoniucci et al 2014b). Using the assumption that the same relationships between L line vs. L acc also hold in the more embedded class I sources, we can estimateṀ acc in HH34 IRS from the dereddened line luminosities.…”
Section: Mass Accretion Ratementioning
confidence: 99%